Preparation and evaluation of a novel solid dispersion using leucine as carrier. (17th December 2019) - Xia, Xiaojing; Tan, Zeng; Fan, Yaru; Hu, Ying; Deng, Jin
Abstract: Objective: The aim of this study was to develop a novel formulation of oleanolic acid (OA) solid dispersion (SD), using leucine (Leu) as the carrier to improve OA oral bioavailability. Methods: The OA-Leu SD was prepared by solvent evaporation and was evaluated in vitro using differential scanning calorimetry, X-ray powder diffraction, scanning electron microscopy, flowability, hygroscopicity and dissolution test. The stability of the SD was evaluated using accelerated testing. In vivo pharmacokinetic tests were performed in male Sprague Dawley rats using a liquid chromatography tandem-mass spectrometry bioanalytical method. Key findings: OA-Leu SD was successfully prepared, and OA was mostly in an amorphous state. More than 80% of OA could dissolve in OA-Leu SD in 20 min, while only 13.4% of free OA dissolved. The powder flow of OA-Leu SD was clearly improved compared with free OA and its moisture absorption was 3.4%. The accelerated testing further demonstrated that SD could maintain OA in an amorphous state at 40 °C for 6 months. OA-Leu SD showed higher relative oral bioavailability (189.7%) than free OA in rats. Conclusions: Using Leu as a carrier produced a SD with good flowability, low hygroscopicity and high bioavailability.